2005
DOI: 10.1017/s0952523805223052
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases regulate rhabdom morphology in octopus photoreceptors

Abstract: In the cephalopod retina, light/dark adaptation is accompanied by a decrease/increase in rhabdom size and redistribution of rhodopsin and retinochrome. Rearrangements in the actin cytoskeleton probably govern changes in rhabdom size by regulating the degradation/formation of rhabdomere microvilli. Photopigment movements may be directed by microtubules present in the outer segment core cytoplasm. We believe that rhodopsin activation by light stimulates Rho and Rac signaling pathways, affecting these cytoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…We previously reported the immunocytochemical localization of Rho in the rhabdom compartment of photoreceptors from Octopus bimaculoides (Miller et al 2005). Rho, as well as actin, were present along the length of the rhabdomere and suggested that the Rho GTPases were candidates for the regulation of rhabdomere growth and diminution in the dark and light, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported the immunocytochemical localization of Rho in the rhabdom compartment of photoreceptors from Octopus bimaculoides (Miller et al 2005). Rho, as well as actin, were present along the length of the rhabdomere and suggested that the Rho GTPases were candidates for the regulation of rhabdomere growth and diminution in the dark and light, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar = 100 µm A–B, 25 µm C–E. Reprinted with permission from Miller et al (2005) Visual Neuroscience 22 : 295–304.…”
Section: Figuresmentioning
confidence: 99%
See 1 more Smart Citation